A Study of Growth Rate and Seed Yield in Ocimum basilicum Germplasms - Meena, K. C.; Patel, J.; Naruka, I. S.; Haldar, Ajay; Patidar, D. K.; Soni, Nitin (International Journal of Economic Plants, 2022)
The present field experiment was conducted at department of Plantation, Spices, Medicinal and Aromatic Crops, College of Horticulture, Mandsaur in simple Randomized Block Design during 2019-20. This investigation was carried out with twenty germplasms obtained from ICAR-AICRP on MAP, college of Horticulture, Mandsaur. The analysis of variance revealed significant difference in all the growth parameters among the germplasms. However, G19 IC-0622541 recorded maximum leaf area (244.50, 1297.09, 4977.09, 7492.67 and 11461.17 cm2 plant-1), leaf area index (0.321, 1.307, 3.425 and 3.949) and leaf area duration (25.69, 104.57, 273.97 and 315.90 cm2 day-1) during all the growth intervals. While, crop growth rate (0.060, 0.422 g cm-2 day-1) and relative growth rate (0.052, 0.117 g g-1 day-1) were higher till 120 days after transplanting in G19 IC-0622541 but in later stages to harvest G11 IC-0622533 was superior in crop growth rate (1.896, 0.340 g cm-2 day-1) and relative growth rate (0.152, 0.108 g g-1 day-1). G14 IC-0622536 had maximum seed yield (29.57 g plant-1) among the germplasms.